Autism and gambling: A systematic review, focusing on neurocognition. (April 2023) - Chamberlain, Samuel R.; Aslan, Betul; Quinn, Anthony; Anilkumar, Amith; Robinson, Janine; Grant, Jon E.; Sinclair, Julia
Abstract: Autism spectrum disorders (hereafter autism) are prevalent and often associated with elevated rates of substance use disorders. A subset of people who gamble develop gambling disorder, which is functionally impairing. Characterization of relationships between autism and gambling, particularly as relates to cognition, may have important implications. We conducted a systematic review of the literature. Nine out of 343 publications were found eligible for inclusion. Most studies examined decision-making using cognitive tasks, showing mixed results (less, equivalent or superior performance in autistic people compared to non-autistic people). The most consistent cognitive finding was relatively slower responses in autistic people on gambling tasks, compared to non-autistic people. One study reported a link between problem gambling and autism scores, in people who gamble at least occasionally. This systematic review highlights a profound lack of research on the potential neurocognitive overlap between autism and gambling. Future work should address the link between autism and behavioral addictions in adequately powered samples, using validated tools. Highlights: A systematic review of links between gambling and autism was conducted. The most consistent finding was that autistic people may have slower responses on gambling tasks compared to non-autistic people. There was some evidence of an association between problem gambling and autistic traits in a sample of people who gambled at least occasionally. Findings highlight the need for future examination of links between autism and gambling, including cognition, compulsive and impulsive habit mechanisms, as well as gambling behavior in the real world.